A study on fetomaternal outcome in prelabour rupture of membrane conducted at tertiary health care centre at Rajkot, Gujarat, India - Dudhrajia, Kavita; Chauhan, Tinjal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Prelabour rupture of membrane is defined as a rupture of membrane before onset of labour and in the absence of uterine contraction. When it occurs before 37weeks it defined as a preterm PROM. One of the most common complication is preterm delivery approximately 7-10% and account for 1-2% of foetal death. Most commonly associated with subclinical UTI. Methods: A prospective study was conducted from (June 2021-June 2022) at a tertiary health care hospital. All female with spontaneous rupture of membrane after 28weeks of gestation. Results: In present study total 200 cases taken and incidence of department was 6.76%,varies between 2% to18% commonly involved age groups belongs to 20-24 years, at 35 -36 weeks (52%) and with high vaginal delivery rate (approximately) with average baby weight between 2.1-2.5 kg with more than 7 APGAR score, more in multigravida. Conclusions: Incidence of prelabour rupture of membrane can be reduced by early diagnosis of subclinical UTI in antenatal visits.